2020
DOI: 10.3390/foods9091221
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Antioxidant Activity of Thyme, Hemp and Coriander Extracts: A Comparison Study of Maceration, Soxhlet, UAE and RSLDE Techniques

Abstract: Appropriate and standardized techniques for the extraction of secondary metabolites with interesting biological activity from plants are required. In this work, a comparison of different conventional and unconventional extraction techniques (maceration—M, Soxhlet—S, ultrasound assisted extraction—UAE, and rapid solid-liquid dynamic extraction—RSLDE) was investigated. Bioactive compounds were extracted from Thymus vulgaris L. (thyme), Cannabis sativa L. (industrial hemp) and Coriandrum sativum L. (coriander) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
56
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 63 publications
5
56
0
3
Order By: Relevance
“…Nevertheless, PLE is also effective in the extraction of flavones from Thymus species [149], including cirismaritin from T. serpyllum [60], which was also detected in T. Vulgaris after a combination of alternative extraction methods, namely pulsed electric field followed by ultrasound-assisted extraction [153]. A study by Palmieri et al [154], with different conventional methods involving PLE and rapid solid-liquid dynamic extraction, showed that the aforementioned methods obtain better extract yield from T. vulgaris leaves and stems [154]. Subsequently, the extraction of flavones from Thymus residues using these technologies was studied, as seen in the extracts that were rich in flavones derived from steam distillation residues from T. mastichina [155], and the herbal dust and hydrodistillation residue from T. serpyllum and T. vulgaris obtained by PLE, respectively [73,156].…”
Section: Alternative Methods (Environmentally Friendly)mentioning
confidence: 99%
“…Nevertheless, PLE is also effective in the extraction of flavones from Thymus species [149], including cirismaritin from T. serpyllum [60], which was also detected in T. Vulgaris after a combination of alternative extraction methods, namely pulsed electric field followed by ultrasound-assisted extraction [153]. A study by Palmieri et al [154], with different conventional methods involving PLE and rapid solid-liquid dynamic extraction, showed that the aforementioned methods obtain better extract yield from T. vulgaris leaves and stems [154]. Subsequently, the extraction of flavones from Thymus residues using these technologies was studied, as seen in the extracts that were rich in flavones derived from steam distillation residues from T. mastichina [155], and the herbal dust and hydrodistillation residue from T. serpyllum and T. vulgaris obtained by PLE, respectively [73,156].…”
Section: Alternative Methods (Environmentally Friendly)mentioning
confidence: 99%
“…The chemical composition of the TEO has been documented. Thymol has generally been identified to be the main constituent of Thymus vulgaris, accompanied by carvacrol and linalool [28]. These compounds have been stated to have also therapeutic properties (e.g., vs.…”
Section: Introductionmentioning
confidence: 99%
“…UAE waves are transmitted through the liquid medium, damaging the plant wall, resulting in an improved solvent penetration. Therefore, bioactive components can be extracted in minutes [ 28 ]. The presence of heat during isoflavone extractions triggers chemical changes, with the decarboxylation of malonyl-glucosides to acetyl-glucosides and the breakdown of the ester bond being frequently observed, the latter leading to the formation of glucosides [ 26 ].…”
Section: Resultsmentioning
confidence: 99%